Female Representative in Audit Committee and Audit Fees: Evidence from Indonesia - Wahyoedi, Anlika Putra; Andrestio, Stefanny; Yuliati, Retno; Sinaga, Rifeald (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
This research is motivated by the conflicting results of literature discusses on gender in the audit committee on audit fees in Indonesia. The purpose of this study is to analyze the effect of the presence of females on the audit committee on audit fees using the context of Indonesian companies. In addition, this study also discusses the positive relationship on the presence of females in audit committee that strengthens firm inherent situational factors (firm complexity and risk) on audit fees using the Ordinary Least Square (OLS) model. The sample consists of public companies in Indonesia and listed on the Indonesia Stock Exchange (IDX) in the period 2019, 2020 or 2021. The results showed that there was no significant effect of the presence of females on the audit committee on audit fees in Indonesia that can be caused by female characteristics that have converged with male’s characteristics. Thus, females on the audit committee will have the same effect as men in the audit committee. This study contributes to the literature by providing new evidence regarding the relationship of female presence on audit committees to audit fees.